Analysis of Engine Knock Sensor - Daniel Korenciak; Miroslav Gutten; Juraj Adamec; Adam Glowacz; Adam Cichy (Communications - Scientific letters of the University of Zilina, 2018)
The paper deals with design of a simple device for the detection of this disorder. In the beginning of the paper the effect of the undesirable detonation combustion in internal combustion engines is described. An engine control unit monitors these detonations using piezoelectric knock sensors. With the control of these sensors the detonations can be objectively measured just outside the car on the test panels. If this component provides small amplitude of the output voltage it could happen that it would have been in the areas of the engine ignition combustion.